A study of the predators and parasites of Planococcus citri (Risso) (Homoptera) on vines in the Western Cape Province, South Africa - Whitehead, Vincent Booth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1959)
[Introduction] In the Western Cape Province the mealybug, Planococcus citri (Risso), was first reported on vines in 1930 by Joubert (1943a). By 1935 this mealybug had spread to the Hex River Valley, and subsequently to all the main table grape producing areas of the Western Cape Province. At present Pl. citri is the most important insect pest of the table grape industry and can, if not effectively controlled, result in a loss of at least five per cent of the export table grape crop (Kriegler, 1954). Some preliminary work on the natural enemies of Pl. citri on vines was carried out by Stubbings in 1948, but no further work of this nature has been undertaken in this area since then. The fact that the natural enemies can be an effective check to this mealybug on vines in the Western Cape Province has been known for a number of years (Potgieter, 1937; Hattingh, 1943; Joubert, 1943a; Myburgh, 1951). The present work is an attempt to obtain some basic knowlege of the population fluctuations of the insects concerned in this biological control. Surveys undertaken have shown that there is a complex of primary, secondary and possibly tertiary Hynenopterous parasites associated with Pl. citri. The presence of hyperparasites reduces the efficiency of the primary parasitic Hymenoptera. The usefulness of these primary parasites is further reduced as they only occur in effective numbers for a short period of the year. On the other hand, although attacked by some parasites, the numerous coccinellids found preying on Pl. citri are of more importance in reducing the mealybug populations, as they are present on the vines in effective numbers for the greater part of the year.
Keywords: Hemiptera; Parasites; Insect pests -- Biological control; Grapes -- Diseases and pests